2016
DOI: 10.2147/ott.s107771
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic significance of unique ULBPs in pancreatic cancer

Abstract: BackgroundPancreatic cancer is one of the most lethal cancers worldwide, due to the lack of efficient therapy and difficulty in early diagnosis. ULBPs have been shown to behave as important protectors with prognostic significance in various cancers.Materials and methodsImmunohistochemistry and enzyme-linked immunosorbent assays were used to explore the expression of ULBPs in cancer tissue and in serum, while survival analysis was used to evaluate the subsequent clinical value of ULBPs.ResultsStatistics showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Also, serum surface ULBP2 was detectable in lung cancer patients and it also was a prognosis indicator of ovarian cancer and melanoma 5456. It also was a novel tumor marker to evaluate the risk of pancreatic cancer patients 57. RFPL1 is a primate-specific target gene of Pax6, which is notably a key transcription factor for pancreas, eye and neocortex development 58.…”
Section: Discussionmentioning
confidence: 99%
“…Also, serum surface ULBP2 was detectable in lung cancer patients and it also was a prognosis indicator of ovarian cancer and melanoma 5456. It also was a novel tumor marker to evaluate the risk of pancreatic cancer patients 57. RFPL1 is a primate-specific target gene of Pax6, which is notably a key transcription factor for pancreas, eye and neocortex development 58.…”
Section: Discussionmentioning
confidence: 99%
“…The retinoic acid early transcript (RAET) proteins are stress-induced ligands for the immune cell activating receptor NKG2D [29]. While the RAET ligands can signal immune recognition of cancer cells, it is likely that immunosuppression within the microenvironment prevents effective RAET signaling in TCPTC, and the upregulation of NKG2D ligands have been linked to poor prognoses in other cancers [30,31].…”
Section: Resultsmentioning
confidence: 99%
“…Demirkol et al indicated that ULBP2 was a mRNA based stage-independent prognostic marker to prognosticate CC in vivo [ 48 ]. In the analysis of pancreatic cancer, researchers have proved that a high level of soluble ULBP2 is deemed an independent indicator for OS [ 49 ]. In this study, ULBP2 was identified as the unique mRNA outstanding in all three datasets.…”
Section: Discussionmentioning
confidence: 99%